Acute Development Trends of Investment-Construction Sphere - M. A. Plakhotnikova; A. Yu. Anisimov; M. A. Suslova; E. D. Suslov (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The development of various industries during crisis presupposes certain deviations from forecasts made before such situations and it should be taken into account in development strategies of industries. Identifying development trends in the investment-construction sphere during crisis can help correct strategic management of the industry, which forms an acute scientific and practical task. The goal of the research is to identify trends in development of investment and construction sphere to estimate optimum nature of its strategic management. The authors used systematization, classification and statistic analysis as methods of the research. They underline the fact that lately project bank financing has been developing vigorously, which improved safety level of holders’ investment and raised the demand on new homes market. According to the authors the Strategy of innovative development of construction industry in the Russian Federation up to 2030 makes up a fundamental document formulating the vector of its development for decades ahead. The authors came to the conclusion that today investment-construction sphere of the Russian Federation is fast developing industry and it has already restored the growth in indicators after the crisis caused by the corona virus pandemic. The outcome of the research is identified trends in the development of the investment-construction sphere in Russia during crisis and after it.